MECHANISMS OF UPPER AIRWAY OBSTRUCTION IN CHILDREN AND PATHOGENETIC TREATMENT APPROACHES - Катілов, О.В.; Бандурка, Н.М.; Дмітриєв, Д.В. (World of Medicine and Biology, 2014)
In the article modern views on methods of diagnosis and treatment of upper airway obstruction in children are presented. Special attention is paid to the problem of acute constrictive laryngotracheitis. We consider the mechanisms of specified pathology with the focuse on pathogenesis-based treatment modes.
Keywords: upper airway obstruction; acute constrictive laryngotracheitis; disease of young children